2021
DOI: 10.1111/aos.15033
|View full text |Cite
|
Sign up to set email alerts
|

Shared burden is always lighter – Peer‐review performance in an ophthalmological journal 2010–2020

Abstract: Purpose: There are concerns in the academic publishing community that it is becoming more difficult to secure reviews for scientific manuscripts. This study examines trends in editorial and peer review processes in an ophthalmological journal over the last decade. Methods: A retrospective analysis was performed of editorial data from the journal Acta Ophthalmologica containing all manuscript submissions between 2010 and 2020. Results: The number of yearly submissions grew between 2010 and 2019 from 1014 to 162… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Peer review, pivotal to the publication process, is under increasing pressure and prone to many potential biases,891011 but the extent of these biases has been less investigated than other areas of the publication process as most peer review is done anonymously and reviews are not usually in the public domain 1213. Some studies have analysed the selection of peer reviewers and their response to invitations to review submissions to biomedical journals; however, as this information is confidential, these studies have largely been done within single journals and may not be representative beyond their communities 141516. Analyses of published peer reviews and public acknowledgment statements to named reviewers of biomedical journals have shown gender and geographical bias in the contributions 17181920…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peer review, pivotal to the publication process, is under increasing pressure and prone to many potential biases,891011 but the extent of these biases has been less investigated than other areas of the publication process as most peer review is done anonymously and reviews are not usually in the public domain 1213. Some studies have analysed the selection of peer reviewers and their response to invitations to review submissions to biomedical journals; however, as this information is confidential, these studies have largely been done within single journals and may not be representative beyond their communities 141516. Analyses of published peer reviews and public acknowledgment statements to named reviewers of biomedical journals have shown gender and geographical bias in the contributions 17181920…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have evaluated the impact of the pandemic on biomedical peer review activity. Bro et al and Perlis et al compared peer review invitations and agreement patterns in single journals with no focus on gender or geographical inequalities and reported no significant differences in reviewer activity during the pandemic 1532. Hupalo et al found no effect on women’s peer review activity during the pandemic compared with previous years,33 but this was explored in a single journal.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of six journals in the areas of ecology and evolution over the period of 2003–2015 found that the proportion of review invitations that led to submission of review reports had decreased steadily for four of these journals, yet no decline was evident for the other two journals (Fox et al 2017 ). A similar retrospective analysis of editorial data over the period of 2010–2020 from the medical journal Acta Ophthalmologica (the official journal of the Nordic and Dutch Ophthalmological Societies and the European Association for Vision and Eye Research, which attracted an enormous number of submissions—2449—in 2020 alone) indicated an increase in the number of invitations needed to secure peer review (Bro and Hammarfelt 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, no convincing evidence has yet been presented in support of this claim. Further analysis of the data collected for Acta Ophthalmologica, and the four journals in ecology and evolution that had experienced a decline in the reviewers’ willingness to evaluate submissions, showed that the average number of reviews per individual reviewer, or the number of review requests per potential reviewer, had not increased over the examined time frame (Fox et al 2017 ; Bro and Hammarfelt 2022 ). Increases in the number of submissions, as experienced by Acta Ophthalmologica, were offset by increases in rejections without peer review and by a larger reviewer database.…”
Section: Methodsmentioning
confidence: 99%
“…Peer review may become, as a result, biased because editors might then consistently recruit the same “reliable” (i.e., productive) peer reviewers [ 27 ] or those that are known to the editors [ 28 ]. However, placing the burden on a productive sector of the academic community may result in greater refusals to peer review [ 29 , 30 ]. To compound this issue, a positive agreement to review a paper might not necessarily translate into a “gain” for the journal, i.e., a positive outcome of peer review [ 31 ].…”
Section: Publons’ Role In Peer Review Rewards: a Critical Perspectivementioning
confidence: 99%